Transdisciplinary Pedagogical Templates and their Potential for Adaptive Reuse - Dobozy, Eva; Dalziel, James (Ubiquity Press, 2016)
This article explores the use and usefulness of carefully designed transdisciplinary pedagogical templates (TPTs) aligned to different learning theories. The TPTs are based on the Learning Design Framework outlined in the Larnaca Declaration (Dalziel et al. in this collection). The generation of pedagogical plans or templates is not new. However, the creation and sharing of web-based pedagogical templates is underpinned by a re-use philosophy and the notion that such material can be adopted or adapted for various purposes by learning designers and developers. This article will exemplify the importance of pedagogical clarity by showcasing how different teacher and learner roles are instantiated in different TPTs that subscribe to behaviourist, cognitivist, or social learning theories. A key goal is to demonstrate that the TPTs constructed based on the Learning Design Framework (LD-F) introduced in the Larnaca Declaration, are easy to be re-used or modified to suit specific learning situations and contexts.